Message in a Bottle: Scenic Presentation of the Unsayable. (6th May 2020) - Busch, Brigitta
Abstract: Linguistic studies related to trauma are primarily interested in how traumatic events can be verbalized. This article, in contrast, focusses on ways of translating a traumatic experience into forms of symbolization that do not report on what happened but rather foreground the bodily and emotional sensations linked to (re)living such experiences. In discussing such forms of scenic presentation and condensation, I will build, inter alia, on Wittgenstein's (1919/1997 ) distinction between saying and showing as well as on Langer's (1948 ) distinction between discursive and presentational forms of meaning making. The close reading of a multimodal text authored by an eight-year-old schoolgirl in the context of a creative-writing activity allows us to identify poetic and artistic means that suggest a reading of the text as a 'bottled message' about intense feelings of fear and helplessness. In concluding I argue that Bruner's (1986 ) dichotomous distinction between the paradigmatic and the narrative mode of meaning making needs to be extended by recognizing a third mode, which might be termed the presentational mode.